Hubungan Toxic Relationship Terhadap Kesehatan Mental Pada Remaja Di SMK Negeri 1 Lubuk Linggau - Marlina Ulfa; Yance Hidayat; Sasteri Yulianti (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Mental health has been recognized as important for achieving global development goals, as evidenced by its inclusion in the Sustainable Development Goals (SDGs). Poor mental health is a serious health problem, especially among adolescents, with most mental health problems beginning at the age of 14. A toxic relationship is a friendship that is very harmful and causes a person to feel bad. The research method used was descriptive research with a cross-sectional approach, using the Chi-Square statistical test. The sampling technique used was stratified random sampling with a sample size of 210 adolescents at SMK Negeri 1 Lubuk Linggau. The results of the univariate analysis showed that almost half of the respondents (46.7%) experienced toxic relationships, other respondents (16.7%) experienced moderate depression, any other respondents (21.4%) experienced moderate stress, and a small portion of respondents (17.1%) experienced moderate anxiety. The results of the bivariate analysis showed that there was a relationship between toxic relationships and depression in adolescents with p=0.001, there was a relationship between toxic relationships and stress in adolescents with p=0.001, and there was a relationship between toxic relationships and anxiety in adolescents with p=0.001. It is hoped that more attention will be paid to fostering healthy friendships, meaning that no individual will feel harmed by another individual, in order to prevent feelings of anxiety and depression caused by toxic friendships.